Trends in Scope of Practice for Oral Health Care: Future Transformative Effects. (October 2022) - Gordon, S.C.; Riedy, C.A.; Stohler, C.S.; Vujicic, M.
Expert panelists in a think tank format were charged with addressing which ongoing trends will have major effects on dentistry in the future. With reference to literature, they identified and agreed on the following 5 trends affecting the scope of practice and professional interactions: COVID-19, changing demographic and disease patterns, converging technologies and predictive tools, interprofessional primary care, and value-based care payment models. In this article, they give their consensus on how each of these trends is likely to transform oral health care, including a consideration of how the events of 2020 to 2021 modified these trends and how dentistry should respond to them. Chief considerations were how to improve population health, access to care, and quality of care; how to reduce health care disparities and costs; and how to educate and maintain an adequate health care workforce for the future. Knowledge Transfer Statement: The results of this study can help key stakeholders, such as health care facilities, educational and research institutions, insurance companies, and governmental bodies, plan future activities and policies on dental practice and education.